M272 Estimated Cost And Payment By Results (pbr) Tariff Reimbursement For Idiopathic Pulmonary Fibrosis Services Across 14 Specialist Providers In England. (10th November 2014) - Hill, C; Nasr, R; Fisher, MI; Maher, T; Spiteri, M; Allen, M; Birring, S; Parfrey, H; Hoyles, RK; Gibbons, M; Burge, G; Scullion, J; et al.
Abstract : Background: Idiopathic Pulmonary Fibrosis (IPF) is an increasingly important respiratory illness in the UK. Rising prevalence of disease, emerging treatments, development of clinical guidelines for diagnosis and management and a NHS England service specification 1 increase demands on healthcare providers who are required to enhance capacity or reconfigure services to manage patients. Aims: Estimate the patient care pathways across service providers in England compared with pathways recommended by NICE guidelines 2 and the NHS England Service Specification; in terms of time and cost per patient by 'diagnosis', 'management' and 'monitoring', and then levels of reimbursement to providers for current levels of care and those recommended. Methods: Structured interviews with clinicians and coders ascertained current levels of service provision, excluding drug costs, by 14 NHS specialist ILD providers. Data were analysed utilising a bottom-up costing approach to estimate the total pathway costs. Comparison with services and costs as recommended by NICE guidelines and service specification allowed estimation of NHS providers' profit or loss. Results: The estimated mean cost per patient for the first year of diagnosis, management and monitoring was £1, 414, which is approximately £418 (42%) more than is reimbursed by the PBR tariff. 3 By comparison, the equivalent cost of the NICE/service specification pathway is approximately £477 (41%) more than reimbursed by the tariff. In particular, it was noted that significant staff time is required for MDT discussion, but that this is not reimbursed. Conclusions: Results suggest that current NHS tariffs for ILD are insufficient to support current service provision. This is true for current levels of care as well as for the levels of care recommended by NICE. The risks of failure to amend the NHS tariff are: Incomprehensive diagnosis and management may adversely impact patient care and outcomes, at a time when services are under increasing scrutiny and disease prevalence is rising Adverse impact on the financial viability of specialist ILD providers References: http://www.england.nhs.uk/ourwork/commissioning/spec-services/npc-crg/group-a/a14/ http://www.nice.org.uk/Guidance/CG163 https://www.gov.uk/government/publications/national-tariff-payment-system-2014-to-2015